PERSEPSI MASYARAKAT MENGENAI PELAKSANAAN PERAN PERAWAT PUSKESMAS DI PEKANBARU - Yogi Nofrianto; Febriana Sabrian; Sri Utami (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2019)
Nursing services has an important role in implementation of health services in hospitals and health centers. The success of services in Public Health Center is very dependent on performance and the role of nurses in implementing nursing services. Nurses in Public Health Center have six roles and functions, such as service provider, case inventor, as educator, coordinator and collaborator, advisor, as role model. Optimizing the role of nurses is needed wherein nurses must carry out their roles and functions. The aim of this research was to identify public perceptions regarding the implementation of the nurse role in Public Health Center in Pekanbaru. The design of this study was descriptive survey method. The sample of this study was 100 respondents taken from 5 health centers based on inclusion criteria. This study used cluster sampling techniques and univariate analysis to analyze data. The results showed that the community had a positive perception regarding several nurse role. About 71% of the community had positive perception abaut the role of the nurse as coordinator and about 69% had positive perception regarding the role of nurse as collaborator. In addition about 67% of the community had positive perception regarding the role of the nurse as an educator. It is expected that nurses can improve the implementation of the role of nurses and expand the role of nurses that have not been implemented properly. Keywords: Implementation, Public health center, nurses’roles, public pereception.